Real-Life Impact on Lipid Profile of a Switch from Tenofovir Disoproxil Fumarate to Tenofovir Alafenamide in HIV-Infected Patients - Lagoutte-Renosi, Jennifer; Flammang, Mylène; Chirouze, Catherine; Beck-Wirth, Geneviève; Bozon, Fabienne; Brunel, Anne-Sophie; Drobacheff-Thiebaut, Marie-Christine; Foltzer, Adeline; Hustache-Mathieu, Laurent; Kowalczyk, Jakub; Michel, Catherine; Davani, Siamak; et al. (Current HIV Research, 2021)
Background: Tenofovir disoproxil fumarate is a prodrug of tenofovir diphosphate that exposes patients to renal toxicity over the long term. Tenofovir alafenamide, a new prodrug, now makes it possible to reduce toxicity, but at the cost of an alteration in lipid profile. There is currently no recommendation for follow-up of lipid profile when switching from tenofovir disoproxil fumarate to tenofovir alafenamide. Objective: Our study aimed to evaluate the effects on renal function and lipid profile of a switch from tenofovir disoproxil fumarate to tenofovir alafenamide, and the consequences for patient management. Methods: Demographic, clinical and biological data was recorded from a retrospective clinical cohort study in real-life, including patients who switched from tenofovir disoproxil fumarate to tenofovir alafenamide. A descriptive analysis of the study population, with a comparison of biological parameters using the paired Student t test for paired data was performed. Results: From January 2016 to January 2019, a total of 103 patients were included. There was no significant difference in renal function before vs after the switch in therapy (p=0.29 for creatinine, p=0.30 for phosphoremia). We observed a change in lipid profile, with a significant increase in total cholesterol (p=0.0006), HDL cholesterol (p=0.0055) and triglycerides (p=0.0242). Four patients received lipid-lowering therapy after switching. Conclusion: In patients who switch from tenofovir disoproxil fumarate to tenofovir alafenamide, lipid profile is altered, and may require initiation of lipid-lowering therapy. It seems necessary to monitor lipid parameters after this switch, despite the absence of an official recommendation.
Keywords: HIV